A Critical Analysis of Impact of Sleep Deprivation on Emotional Regulation - Singh, Aditi (International Journal of Psychology, 2024)
Purpose: The objective of this paper is to understand the impact of Sleep deprivation on emotional well-being in adolescents. A prevalent issue in modern society, has significant implications for emotional regulation. This study examines the impact of sleep deprivation on emotional processes, highlighting the relationship between inadequate sleep and emotional instability. Methodology: Using a mixed-methods approach, Data was analyzed both quantitative from sleep assessments and emotional response tests, and qualitative data from participant interviews. The data was analyzed using the descriptive statistics. Findings: Results indicate that individuals experiencing sleep deprivation exhibit heightened emotional reactivity, diminished positive affect, and impaired emotional recognition and regulation capabilities. Furthermore, chronic sleep deprivation exacerbates stress and anxiety levels, contributing to long-term emotional dysregulation. These findings emphasized the necessity of adequate sleep for maintaining emotional health and informed interventions aimed at mitigating the adverse effects of sleep deprivation on emotional well-being. Unique Contribution to Theory, Practice and Policy: Future research should explore the minimizing of these effects and develop strategies to promote better sleep hygiene and emotional resilience.